From New Media to New Piety: The Construction of Muhammadiyah Digital Piety Ideas - Mualimin; Tokhirov, Shakhzod; Ramadhana, Nada (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
Muktamar is the highest consultative forum in Muhammadiyah, held every five years to discuss and formulate various decisions about the ummah and nationality issues. At the 48th Muktamar in 2022 in Surakarta, Muhammadiyah discussed six strategic issues, one of which was digital piety. This is very interesting because apart from Muhammadiyah, no Islamic organization in Indonesia has officially made the issue of digital piety a strategic issue to be discussed at its Muktamar. Therefore, this study aims to analyse the construc- tion of the idea of digital piety by Muhammadiyah. This study is qualitative research with a literature study approach. The data was obtained by collecting print and digital literature related to the idea of digital piety by Muhammadiyah. The data obtained were then ana- lyzed using the Miles and Huberman interactive qualitative analysis model. This analysis model has three stages: data reduction, presentation, and conclusion. Analysis of the data obtained leads to two findings. First, digital piety is interpreted by Muhammadiyah as be- having and doing activities in the digital space accompanied by morality and ethics based on Islamic values. Second, three dimensions build the construction of Muhammadiyah’s digital piety ideas, namely the ideological dimension, the normative dimension, and the internalization dimension.